Oral Administration of Escin Inhibits Acute Inflammation and Reduces Intestinal Mucosal Injury in Animal Models - Li, Minmin (Evid Based Complement Alternat Med, 2015)
The present study aimed to investigate the effects of oral administration of escin on acute inflammation and intestinal mucosal injury in animal models. The effects of escin on carrageenan-induced paw edema in a rat model of acute inflammation, cecal ligation and puncture (CLP) induced intestinal mucosal injury in a mouse model, were observed. It was shown that oral administration of escin inhibits carrageenan-induced paw edema and decreases the production of prostaglandin E2 (PGE2) and cyclooxygenase- (COX-) 2. In CLP model, low dose of escin ameliorates endotoxin induced liver injury and intestinal mucosal injury and increases the expression of tight junction protein claudin-5 in mice. These findings suggest that escin effectively inhibits acute inflammation and reduces intestinal mucosal injury in animal models.